White Zimbabwean farmers’ unstable mobilities, identity and history in Douglas Rogers’ The last resort: a memoir of Zimbabwe - Musanga, Terrence (Taylor & Francis (Routledge, 2016)
White displacement as a consequence of Zimbabwe’s land reform programme resulted in white economic and social mobilities and the need to reconfigure identities and preserve white Zimbabwean farmers’ history and memory as reflected in Douglas Rogers’ The last resort: A memoir of Zimbabwe (2009). This dislocation provokes a fear of loss of memory and history in the white Zimbabwean community and therefore triggers a desire to preserve history and memory, which are central in identity formation. In addition, the preservation of history and memory acts as an important site for the contestation of the land reform programme, identity and belonging.